Clinical Use of Degludec in Children and Adolescents with T1D: A Narrative Review with Fictionalized Case Reports - Thalange, Nandu (Diabetes Ther, 2019)
The use of insulin in children and adolescents with type 1 diabetes (T1D) is a challenge because of the heterogeneity of these patients and their lifestyles, with consequent unpredictability in blood glucose levels. A new ultra-long-acting basal insulin, insulin degludec (degludec), has the potential to mitigate some of these challenges, notably variability in the glucose-lowering action of the basal insulin component of an insulin regimen, and consequent risks of hypo- and hyperglycemia. However, the protracted half-life and steady state pharmacokinetics of degludec potentially bring some new challenges. In particular, the adjustment of therapy in response to commonly encountered clinical situations might require a different approach when degludec is used in place of other currently used basal insulins in this challenging patient population. The purpose of this article is to guide clinicians through a series of case histories in the use of this insulin. These include, but are not limited to, how to initiate, titrate, switch from other basal insulin or pump therapy; how to alleviate difficulties arising as a result of unpredictable lifestyle/habits; and how to maintain treatment following diabetic ketoacidosis. The guidance presented in this review illustrates that degludec is a good option for a diverse range of children and adolescents with T1D, providing much needed flexibility in the treatment of this challenging patient population. Funding Novo Nordisk.